Effect of nitrogen and phosphorus application on starch characteristics and quality of rice with different nitrogen efficiency - Yang, Guotao; Wang, Qin; Zhang, Guohao; Jiang, Chunyan; Ma, Peng; Hu, Yungao (Frontiers in Nutrition, 2024)
The application of nitrogen and phosphorus fertilizers is an important factors affecting the quality of rice, and different nitrogen-efficient rice varieties show significant differences in their response to nitrogen and phosphorus application. In this experiment, a lownitrogen-high efficiency variety (Deyou 4727) and a high-nitrogen-high efficiency variety (Jingyou 781) were selected, and the changes in rice quality and differences in starch structure under nitrogen-phosphorus interaction treatments were determined. Appearance, flavor, starch content and thermodynamic properties, endosperm cell arrangement, and starch granule morphology and size were significantly influenced by variety, nitrogen-phosphorus interactions, and their interaction effects. The effect of nitrogen fertilizer on quality was greater than that of phosphorus fertilizer. The whiteness and chalkiness rates of Deyou 4727 first decreased and then increased with increasing nitrogen fertilizer application, wheras the appearance quality of Jingyou 781 increased with increasing nitrogen fertilizer application. Starch crystallinity in Deyou 4727 first increased and then decreased with increasing nitrogen fertilizer application, whereas starch crystallinity in Jingyou 781 increased continuously with increasing nitrogen fertilizer application. The application of phosphorus fertilizer led to an increase in starch crystallinity in both nitrogen-efficient rice varieties, consistent with the response of different rice varieties to nitrogen and phosphorus in terms of appearance and chalkiness. With the increasing application of nitrogen and phosphorus fertilizers, the differences in the physicochemical properties and structure of starch became more significant. High-nitrogenefficient rice varieties can significantly improve appearance quality under high nitrogen conditions, and the interactions of medium-high nitrogen and low-medium phosphorus can lead to a significant decrease in starch thermal parameters and retention rate, thus improving rice cooking quality. Low-nitrogen-efficient rice varieties can also improve the quality of rice under low-medium-nitrogen conditions with appropriate application of phosphorus fertilizer.